The Effectiveness of Law Enforcement in Accountability for Blasphemy Crimes: (Study Decision Number: 365/Pid.Sus/2023/PN Idm) - Nazhif Haykal Andeni; Lesmana, Sri Jaya; Ratna Indayatun (The International Journal of Law Review and State Administration, 2025)
Religious blasphemy is an act of insulting or demeaning religious beliefs. In such cases, law enforcement must apply the law and take action against violations through both litigation and non-litigation. However, in Decision 365/Pid.Sus/2023/PN IDM, the legal measures were deemed insufficient to create a deterrent effect, as they only imposed criminal responsibility on the perpetrator. To address this, an ultra petita decision is necessary, where the judge imposes a stronger sentence to prevent future offenses. Judge Panji Gumilang, in handling a similar case, can refer to the jurisprudence from the Ahok blasphemy case as a legal basis, ensuring that the verdict carries a stronger deterrent effect and upholds justice more firmly.